HUMANBEINGS IN ISLAM AND THEIR IMPLICATIONS IN EDUCATION - Sutiono Sutiono (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
In Islam, humans are entities with two dimensions: the material dimension (body) and the immaterial dimension (soul, spirit, mind, etc.). The body will perish with death, while the soul remains and will be resurrected on the Day of Judgment (Qur'an, Yasin 36:78-79). Humans are noble creatures, even more noble than angels (Qur'an, al-Hijr 15:29). Furthermore, humans are the only beings that receive significant attention in Islam, as evidenced by the numerous verses in the Qur'an that discuss humans from various aspects, including the different names given in the Qur'an to refer to humans, such as insan, ins, al-nas, unas, and basyar, and their implications in education. The method or approach used in this research is qualitative. Qualitative research explains and analyzes phenomena, events, social activities, attitudes, and perceptions of individuals or groups toward something. Qualitative research is scientific research that emphasizes the natural characteristics of the data sources. Based on the results of the research and analysis from various literature sources, the Islamic concept of human nature, as expressed by the terms al-insan, al-nas, and al-basyar, provides a balance between human rights and obligations as individuals, social beings, and cultural entities, as creatures of Allah SWT. Thus, if Islamic education only emphasizes the formation of a Muslim personality capable of devotion, worship, and possessing noble character, it will only produce individual piety while neglecting the mastery of science and technology. Consequently, scientific and technological advancements will be dominated by other communities. Conversely, if Islamic education focuses solely on forming a caliph on earth capable of mastering science and technology to manage nature for worldly prosperity, without balancing their role as servants of Allah SWT, humans may become intelligent but their souls and hearts will be devoid of divine light. Therefore, Islamic education should aim to develop the full potential of humans in concrete forms, possessing competencies that include both hard and soft skills. The three domains of education, namely cognitive, affective, and psychomotor, should be achieved, so the outcome of Islamic education becomes perfect.